Psychological Capital as a Function of Career Streams - Ms. Sai Shrikant Joshi (International Journal of Indian Psychȯlogy, 2022)
The present study aims at assessing the psychological capital of the HSC students from arts, commerce and science stream. Sample of N=42 from each of three streams was collected. The Students Psychological Capital Scale, a smaller version of the Psychological Capital Questionnaire developed by Luthans was used for measurement of PsyCap. One way ANOVA was performed on the scores of the sample. The HSC students from arts, commerce and science stream did not significantly differ on PsyCap. But commerce students show significantly high PsyCap as compared to arts students.